Experimental and Molecular Dynamics Simulation Study on Sulfate Corrosion Resistance of Cellulose-Nanocrystal-Modified ECC - Lei Yu; Xiaolong Xu; Songyuan Ni; Dan Meng; Xue Meng; Binghua Xu (Applied Sciences)
In this study, cellulose nanocrystals (CNs) were utilized to enhance the mechanical properties and sulfate corrosion resistance of engineered cementitious composites (ECCs). The results of compressive strength and uniaxial tensile tests demonstrated that the incorporation of CNs significantly improved the compressive strength, strain rate, tensile strength, and sulfate corrosion resistance of ECC specimens. Scanning electron microscopy (SEM) observations revealed that the addition of CNs facilitated the formation of increased amounts of ettringite and calcium silicate hydrate (C-S-H) in the matrix, enhancing the hydration degree of the cementitious system and increasing the overall density of the ECC structure. Molecular dynamics simulations were employed to investigate the interactions between CN, C-S-H, water molecules, and sulfate ions (SO42−) while also calculating the kinetic parameters of atoms at the interface. These simulations provided insights into the microstructural strengthening mechanism of CNs in improving the sulfate corrosion resistance of ECCs. The results indicated that CNs adsorb onto C-S-H via Ca-O and H-O coordination, forming a protective layer that inhibits the penetration of SO42− and water molecules into the C-S-H structure. Additionally, CNs form hydrogen bonds with SO42− and water molecules, which restricts their diffusion and reduces their coordination with the C-S-H interface and the dissolution of SO42− and water to the hydration product, thereby enhancing the sulfate corrosion resistance of ECCs.